An Inquiry into Lexical Cohesive Elements in the Story of Gaumart - Abbas-Ali Vafaie; Davood Sparham; roghayeh kardelilvari (Matn/Pizhūhī-i Adabī, 2017)
Coherence is achieved through creating a link between words and sentences which have specific content and meanings. Hence, the meaning is clarified through the meaningful relationships between the textual elements of a text. Cohesive factors are of the three types, namely, syntactic, lexical and relational. The present study aims at investigating lexical cohesion in the story Gaumart based on Halliday and Hasan’s Theory. The study had a descriptive and secondary research approach. The results of the study showed that the poet has been able to create close ties between different elements of the text through the application of lexical elements, especially repetitive ones.